(untitled) (Sinología hispánica. China Studies Review, 2021)
Kinship is one of the most basic principles of society, based on marriage and blood, and as we all know, the kinship system in Chinese is the most complicated of the known languages, but the Shang Dynasty system (ca 1600 BC - 1046 BC) was very different from those of later generations and today. The Inscriptions on Shell and Bones is an important first-hand corpus to get closer to the Shang dynasty. Among the plates recovered, on the terms related to the meaning of “spouse”, find: